Challenging the binary of home vs. host state governance: Canadian transnational mining behavior and local communities in the Philippines extractive industry. (December 2022) - Asuncion, Angela M.; Ubaldo, John Edison T.; Caouette, Dominique; Besmanos, Beverly; Brunet, Nicolas D.
Highlights: Canadian Neocolonial Mining in the Philippines. Corporate Social Responsibility in the mining industry. Red-tagging and the vilification of dissent. The Tribal Dealer & The Politics of Indigeneity. Abstract: As the world's dominant actor, the Canadian mining industry has historically been scrutinized for its socio-environmentally egregious operations in the Global South, particularly in mineral-rich nations, such as the Philippines. Canadian multi-national corporations are known for causing extensive ecological devastation; contaminating critical watersheds; and exhausting areas of its culturally valuable resources. With over 60 percent of large-scale mines operating in ancestral territories in the Philippines, clashing worldviews on land ownership have driven violent confrontations between Indigenous and local communities, national governments, and corporations. This exploratory study examines Canadian corporate mining behaviors in the Philippines. This study employs an action-oriented research approach applied to a single qualitative macro-level case study. Utilizing document review and semi-structured key informant interview methodologies, the research results indicate that international and domestic actors have used the legal system favoring corporate interests to suppress mining resistance and advance neoliberal modes of extraction.